BRAGA JR, Amaro Xavier; SILVA, Valéria Fernandes da (Orgs.) Representações do Feminino nas Histórias em Quadrinhos. Maceió: Edufal, 2015. 330 p. - Zanin, Maycon André (História, histórias, 2016)
BRAGA JR, Amaro Xavier; SILVA, Valéria Fernandes da (Orgs.) Representações do Feminino nas Histórias em Quadrinhos. Maceió: Edufal, 2015. 330 p.